2021
DOI: 10.31925/farmacia.2021.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Plant Products and Their Inhibitory Activity Against Xanthine Oxidase

Abstract: Plant phytochemicals are very extensive and varied sources for medicinal compounds. The need for finding alternative remedies for several illnesses that are linked to the products of an enzyme like xanthine oxidase, motivates researchers to find in nature searching for local new better remedies. Many plants' extracts are investigated, and many other sources like honey, food, and bacteria are being found to produce inhibitors of xanthine oxidase. Yet efforts are needed to find the perfect remedy with clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Finally, it has been reported that the methanolic leaves extract of A. hierochuntica exhibited XO inhibitory properties as it encompasses the presence of different flavonoid group. Likewise, many plant extracts rich in secondary metabolites known to reduce XO catalytic activity are systematically reviewed [23,39]. Furthermore, reports on the planar structure of flavonoids [40], and the induction of conformational change in the active site of XO rationalize the role of flavonoids as a potential XO inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been reported that the methanolic leaves extract of A. hierochuntica exhibited XO inhibitory properties as it encompasses the presence of different flavonoid group. Likewise, many plant extracts rich in secondary metabolites known to reduce XO catalytic activity are systematically reviewed [23,39]. Furthermore, reports on the planar structure of flavonoids [40], and the induction of conformational change in the active site of XO rationalize the role of flavonoids as a potential XO inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Pada tahap fraksinasi, campuran dua jenis pelarut pada setiap rasio memiliki sifat polaritas yang berbeda. Sifat polaritas pelarut dapat ditentukan dengan nilai konstanta dielektrik [8,17]. Semakin tinggi nilai konstanta dielektrik maka semakin tinggi juga sifat polar sebuah pelarut.…”
Section: Hasil Dan Diskusiunclassified
“…Potensi interaksi ikatan hidrogen antara gugus 5-OH dan gugus Mo-OH kemungkinan membantu mengorientasikan kuersetin tetapi tidak berkontribusi secara signifikan terhadap pengikatannya yang erat. Struktur kristal saat ini menunjukkan bahwa gugus C-4 karbonil dan 3-OH dari kuersetin terlibat dalam interaksi ikatan hidrogen dengan gugus karboksilat rantai samping Glu 802 enzim, meskipun beberapa studi kinetik menyimpulkan bahwa 3 gugus -OH tidak memberikan kontribusi yang signifikan terhadap afinitas pengikatan [8,30].…”
Section: Hasil Dan Diskusiunclassified
See 1 more Smart Citation
“…Flavones and flavonols have higher potential as competitive inhibitors than other flavonoid groups because hydroxyl group is easier to capture electrons from the active site of the xanthine oxidase [6]. The bioactive plant components as luteolin, quercetin, isorhamnein, chrysin, galangin, cajaninstilbene acid, and prosapogenin inhibit xanthin oxidase more effectively than allopurinol [7].…”
Section: Introductionmentioning
confidence: 99%